Unsur Naratif Pada Permainan Seluler “Selera Nusantara – Episode: Nasi Goreng” - Setiawan, Fredy Nugroho (Fakultas Ilmu Budaya Universitas Mulawarman, 2024)
“Selera Nusantara” is a mobile simulation game from Indonesia. The game not only offers cooking simulation challenges for the players but also provides information about the main characters who appear between game levels. The existence of story elements in the permainan seluler is the focus of this research. In this case, we chose “Selera Nusantara – Episode: Nasi Goreng” as the object of study. This research is about how the narrative aspect in the permainan seluler